Re-recognition of BMPR1A-related polyposis: beyond juvenile polyposis and hereditary mixed polyposis syndrome. (5th January 2023) - Zhao, Zi-Ye; Lei, Ye; Wang, Zhao-Ming; Han, Huan; Xing, Jun-Jie; Xu, Xiao-Dong; Gao, Xian-Hua; Zhang, Wei; Yu, En-Da
Abstract: Background: Bone morphogenetic protein receptor type 1A ( BMPR1A ) is responsible for two individual Mendelian diseases: juvenile polyposis syndrome and hereditary mixed polyposis syndrome 2, which have overlapping phenotypes. This study aimed to elucidate whether these two syndromes are just two subtypes of a single syndrome rather than two isolated syndromes. Methods: We sequenced the BMPR1A gene in 186 patients with polyposis and colorectal cancer, and evaluated the clinicopathological features and phenotypes of the probands and their available relatives with BMPR1A mutations. Results: BMPR1A germline mutations were found in six probands and their three available relatives. The numbers of frameshift, nonsense, splice-site, and missense mutations were one, one, two, and two, respectively; two of the six mutations were novel. Typical juvenile polyps were found in only three patients. Two patients had colorectal cancer rather than any polyps. Conclusions: Diseases in BMPR1A germline mutation carriers vary from mixed polyposis to sole colorectal cancer, and typical juvenile polyps do not always occur in these carriers. The variety of phenotypes reflected the features of BMPR1A -mutation carriers, which should be recognized as a spectrum of one syndrome. Genetic testing may be a good approach to identifying BMPR1A -related syndromes.